Proactive budgeting: choosing a development vector in the context of digitalization - N. S. Sergienko (Вестник университета, 2025)
The article examines the features of the development of proactive budgeting, officially introduced in the Russian Federation 10 years ago, in the context of digitalisation with consideration to regional and municipal specifics. In pursuit of the goals of involving citizens in the budget process and increasing their role in managing local finances, initiative budgeting projects have extensive practice in terms of the introduction and application of various management and information technologies. A competitive approach in the selection of the projects based on evaluation according to specified criteria allows them to be flexible and adaptable to local needs. The possibility of applying differentiated approaches to the proactive budgeting allows authorities to develop regional models, the effectiveness of which also depends on coordination of efforts between these bodies of power, public organisations and citizens with consideration to the local peculiarities. The article focuses on the analysis of advantages and risks of introducing digital technologies into the process of forming and implementing initiative projects. The key types of risks, including social, technological, political, economic, legal, organisational and reputational ones, are identified, and measures to minimise them are proposed. The article highlights the need for an integrated approach, including modernised digital infrastructure, better transparency and process security as well as improvement of the regulatory framework with consideration to Russian practices. The introduction of a balanced approach to digitalisation of the proactive budgeting will strengthen democratic processes, increase the efficiency of budget use and create conditions for equal participation of citizens in decision-making at the municipal level.